EXPERIMENTAL INVESTIGATIONS OF SNOW BANK FORMATION DURING MILLING AND ROTARY SNOW BLOWER OPERATION - Sergeevich Aleshkov, Denis; Viktorovich Banket, Mikhail; Vladimirovich Sukovin, Mikhail; Slavent'evich Bakunov, Alexander; Vladimirovich Shapoval, Dmitriy (Journal of Applied Engineering Science, 2021)
The main purpose of this paper is to identify basic regularities of snow bank formation when using milling and rotary snow blowers. The study of the mechanism of snow bank formation was based on experimental investigations of the throwing machine rotor of the low-powered milling and rotary snow blower. Moistened sawdust was used as artificial snow. As the result of the conducted investigations, the nature of the snow bank formation has been determined and the regression equations for the distribution of the number of particles, total mass and average mass of individual particles of the material simulating one specific type of snow along the length of the snow bank have been obtained. The relative amount of the material transported by the rotor in relation to the total amount of material loaded into the rotor for the specified geometric and kinematic parameters of the rotor of the throwing machine has been found. The dependencies obtained make it possible to carry out simulation and visualization of snow bank formation during snow clearing operations, to choose the most rational parameters of the throwing machine of the milling and rotary snow blower, as well as to specify the strategy of snow clearing operations with the application of milling and rotary snow blowers.